Edukasi Gizi Seimbang Untuk Pencegahan Stunting Pada Ibu Hamil Dan Balita Di Desa Binaan - Nurhaedah, Nurhaedah; Rahmat, Rezqiqah Aulia; Bahrun, Suriani; Wati, Isra; Aripa, Lusyana; Pramono, Edi; Setiawati, Eka (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Stunting is a chronic nutritional problem that remains a major challenge in Indonesia, particularly in rural areas with limited access to nutrition education, sanitation, and health services. This community service program aims to improve the knowledge of pregnant women and mothers of toddlers regarding balanced nutrition as a means of preventing stunting in Assisted Village X. Activities included balanced nutrition counseling, demonstrations on making nutritious complementary foods (MP-ASI), screening for toddler nutritional status, and mentoring families at risk of stunting. A total of 65 participants (22 pregnant women and 43 mothers of toddlers) participated in the program. Results showed an increase in participant knowledge, with an average pre-test score of 55.3, rising to 86.1 in the post-test. Furthermore, 12 toddlers at risk of stunting were identified and provided with further mentoring. The program also encouraged the formation of